A propósito do mal em Hannah Arendt - Lessa, Kaique Sildo Oliveira (2020)
This work aims to analyze Hannah Arendt’s thought on evil. This is one of the main questions that permeate the author’s work, which she proposed to think about because she had experienced the horrors of totalitarian regimes, but especially when she discovered the actions of Nazism in the period of the Second World War. The construction of the argumentation follows three aspects of evil: radical evil, thought by Kant, absolute evil and the banality of evil, thought by Hannah Arendt. The first moment will be developed from the analysis about radical evil thought by Kant in his work Religion within the Limits of Reason Alone (1793), an evil that has its origin in a propensity of human nature. We will see that Hannah Arendt uses Kant’s thesis as a basis, but later formulates her own view of evil. In the second step, we will examine the relationship between totalitarian regimes and absolute evil, cited by our author in her work The Origins of Totalitarianism (1951). At this point, we will see her analysis of totalitarianism as a form of government that defies all understanding existing in tradition. Totalitarianism assumes power through massification and propaganda, it governs on the basis of ideology and terror and creates concentration camps as mechanisms for the mass destruction of human beings, with Jews as “objective enemies”. Understanding these aspects is extremely important, as they are the source of absolute evil, whose main effects are the superfluity and the destruction of the person in all his/her characteristics. At the end, our reflection turns to the banality of evil, a concept formulated from Hannah Arendt’s observations of the Adolf Eichmann trial in Israel, a Nazi whose function was to send Jews to concentration camps. At this point, we will pay attention to the problems encountered in the trial to deal with this new type of criminal as well as the analysis of responsibility, both of them important for understanding the banality of evil. The dissertation concludes the investigation with a study on banal evil, where we wonder if it would be something new or an extension of radical evil.